Land Subsidence of Java North Coast Observed by SAR Interferometry. Issue 1 (October 2021) - Sidiq, T P; Gumilar, I; Meilano, I; Abidin, H Z; Andreas, H; Permana, A
Abstract: Land Subsidence became recent issue in environmental management in Indonesia. Large cities in Indonesia, especially in Java Island, are well known to suffer from fast rate land subsidence such as Jakarta, Bandung, and Semarang. However, the phenomena is presumed to also happen in other cities which have large industries and located on the deposit or clay soil layer. The effect of land subsidence may be different in some location, but the coastal zone will have more impact since land subsidence will also induce tidal flood and may cause land area reduction. In this study, we use more than 70 Sentinel-1 data, range from year 2016 to 2020 to map the land subsidence in the Java North Coast. The interferograms are selected based on Small Baseline Subset (SBAS) algorithm. National Digital Elevation Model (DEMNAS) is used in differential InSAR process. Our result shows that many cities along the Java North Coast suffer land subsidence. Jakarta, experience has maximum subsidence more than 5 cm/year. In Central Java, Pekalongan experience up to 7 cm/year of land subsidence, while Semarang and Demak has subsidence rate up to 8 cm/year.